EU Copyright Law, Lobbying and Transparency of Policy-making: The cases of sound recordings term extension and orphan works provisions - Vetulani-Cęgiel, Agnieszka (My University, 2015)
The objective of this paper is to discuss EU lobbying in the area of copyright. Legislation needs to regulate the legal position of various different stakeholders in a balanced manner. However, a number of EU copyright provisions brought into effect over recent years were highly controversial and have led to suggestions that powerful lobbying forces may have had some influence. This article investigates the effects of lobbying on copyright lawmaking in Europe. A specific comparative and multifaceted analysis is provided of the legislative process for two recently adopted directives: 2011/77/EU which extends the term of protection of sound recordings and 2012/28/EU which introduces certain permitted uses of orphan works (some references are also made to the ACTA case). Firstly, a short presentation is given of the legal bases for the EU consultation process and lobbying. Next, an analysis is provided of the two cases, taking into consideration the policy-making procedures (with special focus on how the consultation process was handled), the legal solutions proposed and adopted and the various stakeholders’ claims. Lastly, it asks why some interest groups were successful and some others failed (the analysis identifies two types of factor for the effectiveness of lobbying: those resulting from stakeholders’ actions and those connected with the consultation process).
Keywords: Copyright; Law-Making; Policy-Making; Interest Group; Lobbying; Stakeholder; Consultation; Transparency; Orphan Work; Sound Recording; Phonogram; EU; Library; Music